Study of the Association of V640L (rs6133) Polymorphism in the Platelet P-selectin Gene with Acetylsalicylic Acid Resistance in Patients after Coronary Bypass Surgery - A. A. Kosinova; T. S. Mongush; M. D. Goncharov; T. N. Subbotina; K. S. Semashchenko; G. Y. Kochmareva; Yu. I. Grinshtein (Рациональная фармакотерапия в кардиологии)
Aim. To study the association of V640L (rs6133) polymorphism in the P-selectin gene with acetylsalicylic acid (ASA) resistance in patients with coronary heart disease after coronary bypass surgery (CABG).Material and methods. The study included 104 patients aged 36-78 years (mean age 61.6±6.9 years) with stable angina pectoris: 61 (58.7%) patients had functional class II (according to Canadian Cardiovascular Society), 41 (39.4%) – class III and 2 (1.9%) – class IV. Atherosclerotic lesions of the coronary arteries were confirmed by coronary angiography. The antiplatelet therapy was stopped for at least 5 days before CABG. In the postoperative period, from the first day, all patients received 100 mg of ASA in enteric form, 61 patients received alone ASA therapy, 43 patients – combined antiplatelet therapy: ASA+clopidogrel (75 mg/day). The aggregation study was performed with an optical aggregometer, using 5 μM adenosinediphosphate (ADP) and 1 mM arachidonic acid inductors before CABG, on 1-3 day and on 8-10 day after surgical treatment. DNA samples were examined for the V640L (rs6133) polymorphism in the P-selectin gene by real-time polymerase chain reaction (PCR) using the allele-specific primers.Results. The frequency of the homozygous GG genotype of the rs6133 polymorphism was 84.6%; heterozygous GT genotype – 15.4%. The amplitude of aggregation with ADP before CABG, on 1-3 day and on 8-10 day after CABG for carriers of homozygotes of allele G vs carriers of the allele T were: 47.9±19.3%, 44.5±17.8%, 30.1±13.2% vs 47.9±17.1%, 46.3±16.5%, 39.6±22.0%, respectively (p=0.497, 0.441 and 0.687, respectively). The amplitude of aggregation with arachidonic acid before CABG, on 1-3 day and on 8-10 day after CABG for carriers of homozygotesof allele G vs carriers of the allele T, were: 47.9±23.2%, 24.5±21.7%, 12.3±16.3% vs 54.3±17.8%, 29.7±23.7%,  11±10.9%, respectively (p=0.416, 0.825 and 0.872, respectively). In the first 10 days of the postoperative period, 6 thrombotic events (5.7%) were observed in the study group: 2 strokes and 4 perioperative myocardial infarctions. Five events occurred in the group of patients with the GG genotype, 1 event in the group of patients with the GT genotype.Conclusion. V640L (rs6133) polymorphism in the P-selectin gene is not associated with ASA resistance in patients with coronary artery disease after CABG. The T allele of the rs6133 polymorphism is not associated with increased platelet aggregation activity after CABG and does not increase the risk of adverse events in the first 10 days after CABG.